From the Genesis to the Project Result: The Success of Design for Place Branding also Depends on the Modality of Contracting - Ribeiro, Emílio; Raposo, Daniel; Menezes, Marizilda [UNESP] (Springer Nature, 2020)
This chapter results from a research on place branding, within the scope of the Doctoral Program in Design of the School of Architecture of the University of Lisbon, referring to partial results of the research, specifically on contracting models of designers responsible for the design of place branding brands. Therefore, cases are analyzed from the hiring modality and points are presented for hiring improvements. The methodology is qualitative and descriptive, based on the literature review. The chapter assumes that among the determining factors for the success of a brand branding design is the hiring modality. Direct or indirect, open or restricted, they are aspects little considered when defining the demand for a place branding. One observes the importance of a modus operandi of who does and how does the contracting to minimize the failures. As a result, it was observed that the briefing should be associated with other tools for a better understanding of the territory, as well as a parametric analysis of existing brands to avoid plagiarism or similarity. The singularities of the place should be considered to give it authenticity, effectiveness and sustainability. On the other hand, the result of the design of the brand passes through a rigorous research on the territory, its image and its identity that determined the (re) positioning of the place.
Keywords: Branding design; Hiring mode; Place branding